Correlates of Voting Participation of People with Intellectual and Developmental Disabilities. Issue 3 (2nd October 2017) - Friedman, Carli; Rizzolo, Mary C.
ABSTRACT: People with intellectual and developmental disabilities (IDD) vote less frequently than nondisabled people and people with other disabilities. This study explores what factors facilitate and hinder people with IDD's voting participation. To do so, 1, 341 people with IDD were surveyed using the Personal Outcome Measures®. Binary logistic regressions revealed significant relationships between voting participation, and support needs, residence types, guardianship statuses, and organizational supports. Along with the right supports, attention to barriers that might exist can ensure people with IDD are able to make use of their civil rights and participate in this crucial form of civic engagement.